Thermodynamic analysis of a novel dual-loop organic Rankine cycle for engine waste heat and LNG cold. (5th May 2016) - Sung, Taehong; Kim, Kyung Chun
Highlights: A novel dual ORC system is designed for engine waste heat and LNG cold. Exhaust gas and jacket cooling water are considered as heat sources. LNG and boil-off gas are considered as heat sinks. ORC loops are optimized to produce the maximum net work output. Abstract: The marine sector produces a large portion of total air pollution, so the emissions of the engines used must be improved. This can be achieved using a new eco-friendly engine and waste-heat recovery system. A dual-fuel (DF) engine has been introduced for LNG carriers that is eco-friendly and has high thermal efficiency since it uses natural gas as fuel. The thermal efficiency could be further improved with the organic Rankine cycle (ORC). A novel dual-loop ORC system was designed for DF engines. The upper ORC loop recovers waste heat from the exhaust gas, and the bottom ORC loop recovers waste heat from the jacket cooling water and LNG cold. Both ORC loops were optimized to produce the maximum net work output. The optimum simple dual-loop ORC with n-pentane and R125 as working fluids produces an additional power output of 729.1 kW, which is 4.15% of the original engine output. Further system improvement studies were conducted using a recuperator and preheater, and the feasibility of using boil-off gas as a heat sink was analyzed. Optimization of the system configuration revealed that the preheater and recuperator with n-pentane and R125 as working fluids increase the maximum net work output by 906.4 kW, which is 5.17% of the original engine output.